Self-excited chaotic dynamics of a nonlinear thermo-visco-elastic system that is subject to laser irradiation - Hollander, E.; Gottlieb, O. (Applied physics letters, 2012)
We derive and investigate a continuum mechanics based low-order dynamical system for a nonlinear thermo-visco-elastic cantilever that is subject to laser irradiation. The model consists of a Fabry–Pérot interferometer where heat transfer between cantilever layers creates a photothermal effect that triggers self-excited oscillations. Model validation is demonstrated by comparison of results to those of a benchmark experiment [K. Hane and K. Suzuki, Sens. Actuators, A 51, 179–182 (1996)] that exhibited periodic oscillations near a subcritical Hopf bifurcation. A numerical analysis reveals a dense chaotic bifurcation structure foliated by multiple periodic solutions. This analysis of a validated continuum based model culminates with a photothermal strange attractor where radiation pressure is negligible.